ApoA-I-Mediated Lipoprotein Remodeling Monitored with a Fluorescent Phospholipid - Edward B. Neufeld; Masaki Sato; Scott M. Gordon; Vinay Durbhakula; Nicolas Francone; Angel Aponte; Gizem Yilmaz; Denis Sviridov; Maureen Sampson; Jingrong Tang; Milton Pryor; Alan T. Remaley (Biology, 2019)
We describe simple, sensitive and robust methods to monitor lipoprotein remodeling and cholesterol and apolipoprotein exchange, using fluorescent Lissamine Rhodamine B head-group tagged phosphatidylethanolamine (*PE) as a lipoprotein reference marker. Fluorescent Bodipy cholesterol (*Chol) and *PE directly incorporated into whole plasma lipoproteins in proportion to lipoprotein cholesterol and phospholipid mass, respectively. *Chol, but not *PE, passively exchanged between isolated plasma lipoproteins. Fluorescent apoA-I (*apoA-I) specifically bound to high-density lipoprotein (HDL) and remodeled *PE- and *Chol-labeled synthetic lipoprotein-X multilamellar vesicles (MLV) into a pre-β HDL-like particle containing *PE, *Chol, and *apoA-I. Fluorescent MLV-derived *PE specifically incorporated into plasma HDL, whereas MLV-derived *Chol incorporation into plasma lipoproteins was similar to direct *Chol incorporation, consistent with apoA-I-mediated remodeling of fluorescent MLV to HDL with concomitant exchange of *Chol between lipoproteins. Based on these findings, we developed a model system to study lipid transfer by depositing fluorescent *PE and *Chol-labeled on calcium silicate hydrate crystals, forming dense lipid-coated donor particles that are readily separated from acceptor lipoprotein particles by low-speed centrifugation. Transfer of *PE from donor particles to mouse plasma lipoproteins was shown to be HDL-specific and apoA-I-dependent. Transfer of donor particle *PE and *Chol to HDL in whole human plasma was highly correlated. Taken together, these studies suggest that cell-free *PE efflux monitors apoA-I functionality.